Criteria for Teaching Performance in Psychology: Invariance According to Age, Sex, and Academic Stage of Peruvian Students - Bazán-Ramírez, Aldo; Pérez-Morán, Juan Carlos; Bernal-Baldenebro, Brando (Frontiers in Psychology, 2021)
The use of scales to assess the performance of professors from the students’ standpoint is a generalized practice in higher education systems worldwide. The purpose of this study is to analyze the factorial structure and measure the invariance of the Scale of Teaching Performance of the Psychology Professor (EDDPsic) among groups according to gender, age and academic stage. The sample of participants was composed of 316 Psychology students from the fourth and sixth semesters (basic cycles), and from the eighth and tenth semesters (disciplinary-professional cycles) of two renowned public universities in Lima, Peru. 231 participants were women (73%), and the mean age of students was 21.5 years old (SD = 2.37). The measurement invariance of the scale in the three study variables was underpinned by a multigroup confirmatory factor analysis conducted using a five-factor model that showed the best fitness indices. It is concluded that significant differences in measuring teaching performance areas of the professor depend on the students’ age difference and on their academic stage (to attend the disciplinary-professional cycles).